2016
DOI: 10.3892/mmr.2016.5906
|View full text |Cite
|
Sign up to set email alerts
|

Identification of serum miRNAs differentially expressed in human epilepsy at seizure onset and post-seizure

Abstract: MicroRNAs (miRNAs) function as potential novel biomarkers for disease detection due to their marked stability in the blood and the characteristics of their expression profile in several diseases. In the present study, microarray‑based serum miRNA profiling was performed on serum obtained from three patients with epilepsy at diagnosis and from three healthy individuals as controls. This was followed by reverse transcription‑quantitative polymerase chain reaction analysis in a separate cohort of 35 health volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
2
19
1
Order By: Relevance
“…Moreover, 10 miRNAs remained regulated for up to 20-28 h in a subgroup of patients that experienced a seizure during sleep. miRNA regulation was also reported by Sun et al (Sun et al, 2016a), who found a correlation between seizure frequency and miR-30a regulation. Although seizure frequency did not affect the plasma miRNA levels in a study with drug-refractory patients (Avansini et al, 2017), the timing of seizure occurrence relative to tissue sampling can be a confounding factor in the analysis and should be monitored and reported in epilepsy biomarker studies.…”
Section: Subject-related Informationsupporting
confidence: 58%
“…Moreover, 10 miRNAs remained regulated for up to 20-28 h in a subgroup of patients that experienced a seizure during sleep. miRNA regulation was also reported by Sun et al (Sun et al, 2016a), who found a correlation between seizure frequency and miR-30a regulation. Although seizure frequency did not affect the plasma miRNA levels in a study with drug-refractory patients (Avansini et al, 2017), the timing of seizure occurrence relative to tissue sampling can be a confounding factor in the analysis and should be monitored and reported in epilepsy biomarker studies.…”
Section: Subject-related Informationsupporting
confidence: 58%
“…To our knowledge there are only four reports investigating serum levels of microRNAs in patients with epilepsy as compared to healthy controls [1215]. Given the great heterogeneity of epilepsy syndromes it becomes clear that additional studies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…We performed a manual literature search in PubMed and the Human MicroRNA Disease Database (HMDD; v3.2) with the combined keywords “FCD, seizures, epilepsy or status epilepticus” and the four upregulated miRNAs (miR-194-2, miR-15a, miR-132, and miR-145), to confirm the relationship between the miRNAs and FCD or different types of seizures and epilepsy [ 52 ] ( Table 2 ). According to the reported literature in PubMed, these miRNAs related to FCD and different forms of seizures and epilepsy [ 30 , 31 , 53 , 54 , 55 , 56 , 57 ] were identified, including the reported evidence of diagnostic and prognostic biomarkers and therapeutic targets ( Table 2 ). Each single miRNA can influence multiple genes.…”
Section: Resultsmentioning
confidence: 99%